Improvement of Mg‐Based Hydrogen Storage Materials by Metal Catalysts: Review and Summary. Issue 33 (6th September 2021) - Yang, Xinglin; Zhang, Jiaqi; Hou, Quanhui; Guo, Xintao; Xu, Guanzhong
Abstract: Magnesium hydride (MgH2 ) has become a very promising hydrogen storage material because of its high hydrogen storage capacity, good reversibility and low cost. However, high thermodynamic stability and slow kinetic performance of MgH2 limit its practical application. In the past few decades, many alternative methods have been designed to solve this problem. A large number of studies have demonstrated that the use of metal catalyst doping modification, MgH2 nanocrystallization and other methods can greatly improve the hydrogen absorption and dehydrogenation performance of MgH2 . Therefore, this paper reviews and summarizes the modification effect of transition metal catalyst doping on the hydrogen storage performance of MgH2, especially the catalysis on the de/rehydrogenation performance of MgH2 . In addition, promoting effects of carbon materials, transition metal alloys and compounds on the hydrogen storage performance of MgH2 were also summarized. Finally, the existing problems and challenges of MgH2 as hydrogen storage materials are discussed, and some possible strategies are proposed. Abstract : In this review paper, we have recorded various metal catalysts with excellent catalytic performance for Mg/MgH2 . The catalytic properties of different types of catalysts were clearly described and summarized in detail. At the same time, some current challenges are pointed out and some possible strategies are given. It is believed that this manuscript can provide some ideas and guidance for researchers who are interested in the field of hydrogen storage in the future.